Korelasi Pernikahan Dini Dengan Perceraian di Desa Simpang Empat Sungai Baru Kabupaten Tanah Laut - Putri, Nadya Ade; Hakim, Arif Rahman (Prodi Sosiologi FISIP ULM, 2024)
Child marriage and divorce are phenomena that occur in many communities in Simpang Empat Sungai Baru Village. This research aims to examine what factors make children choose to marry and eventually divorce. This research uses qualitative research with a phenomenological approach. Data collection used observation, interviews, and documentation. The data analysis technique uses techniques from Miles and Huberman, namely the data reduction stage, data presentation, and conclusion drawing. This research shows that the factors that make children choose to marry are due to pregnancy outside of marriage, immature mindset, economy, and love traps. The tendency of early married couples' households not to last long is due to an immature mindset. The decision to divorce is driven by several factors, such as infidelity, family interference, domestic violence, and exhausted love. AGIL theory states that there are four functions in society so that community life runs stably, namely Adaptation, Goal Attainment, Integration, Latency. Child marriage households in Simpang Empat Sungai Baru Village cannot fulfil the components, only Adaptation because they can adjust the environment. Goal Attainment, Integration, and Latency are not fulfilled because they cannot maintain the marriage and then divorce and also lose trust. Based on the negative impact caused by anum marriage, it is better if the case of anum marriage gets more handling from related parties so that similar cases do not recur.